2021
DOI: 10.1002/jev2.12075
|View full text |Cite
|
Sign up to set email alerts
|

Professional killers: The role of extracellular vesicles in the reciprocal interactions between natural killer, CD8+ cytotoxic T‐cells and tumour cells

Abstract: Extracellular vesicles (EVs) mediate the cross-talk between cancer cells and the cells of the surrounding Tumour Microenvironment (TME). Professional killer cells include Natural Killer (NK) cells and CD8+ Cytotoxic T-lymphocytes (CTLs), which represent some of the most effective immune defense mechanisms against cancer cells. Recent evidence supports the role of EVs released by NK cells and CTLs in killing cancer cells, paving the road to a possible therapeutic role for such EVs. This review article provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 161 publications
0
30
0
Order By: Relevance
“…Subsequently, we found differences in immune characteristics between subtypes. Professional killer cells include NK and CD8+ T cells, which represent some of the most effective immune defense mechanisms against cancer cells; stromal CD8+ T cell density has independent prognostic impact in resected NSCLC and is a good candidate marker (34,35). Tregs can suppress the activation of the immune system, maintain immune tolerance to self-antigens, and contribute to immunosuppression of antitumor immunity, which is critical for tumor immune evasion in epithelial malignancies, including lung cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we found differences in immune characteristics between subtypes. Professional killer cells include NK and CD8+ T cells, which represent some of the most effective immune defense mechanisms against cancer cells; stromal CD8+ T cell density has independent prognostic impact in resected NSCLC and is a good candidate marker (34,35). Tregs can suppress the activation of the immune system, maintain immune tolerance to self-antigens, and contribute to immunosuppression of antitumor immunity, which is critical for tumor immune evasion in epithelial malignancies, including lung cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…by TCR activation ( 66 ). Since the putative role of exosomes and their cargo proteins in the regulation of T cell-mediated immune responses and autoimmune diseases has been recently reviewed by Anel and co-workers ( 67 ) and Del Vecchio and colleagues comprehensively reviewed the role of extracellular vesicles in the interactions between NK cells and CD8 + CTL and tumor cells ( 68 ), we will focus on the potential relationship between intra- and extracellular vesicles in the following. The basis for the close relationship of intra- and extracellular vesicles is the common origin of secretory lysosomes and exosomes from cytoplasmic MVBs.…”
Section: Conceptually Intra- and Extracellular Vesicles Should Not Be Separatedmentioning
confidence: 99%
“…They can meditate crosstalk between immunity and regulate cancer progression. First, B cell-derived exosomes were identified, and then it was found that lymphocytes, dendritic cells (DCs), natural killer cells, mast cells, macrophages, and thymocytes can all produce exosomes [123]. Yan et al has demonstrated that the exosomes of various immune cells contain their origins, target cells, consequences, and involved molecules [124].…”
Section: Role Of Evs In Colorectal Tumorigenesismentioning
confidence: 99%